Analysis and Test of the Transmission Efficiency of Low Speed and Heavy Duty Gearbox - Li Youhua; Li Quancai; Liu Zhongming (Jixie chuandong)
Through the analysis of the influence factors on transmission efficiency of gearbox,a theoretical analysis model of gearbox transmission efficiency is set up from the power consumption,and the influences of gear meshing loss,bearing friction loss,oil loss,oil seal friction loss and windage loss on gearbox transmission efficiency are considered. The analysis model is validated according to the test data of a low speed and heavy duty gearbox,and the influences of speed and torque on the transmission efficiency of gearbox are discussed,the changing curves of gear efficiency with the rotational speed and torque are obtained,the foundation for further research on the efficiency of the gearbox is laid.